Polyamide composition and its use on high-strength transparent polyamide monofilaments
Patent Information
- Application Number
- CN202311374195.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-23
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-10-23
AI Technical Summary
但是该专利中添加氯化钙等金属盐和硬脂酸钙等缚酸剂会导致制成的丝完全不透明
[0029](1)本发明的一种聚酰胺组合物,在相同含水率下,相比于现有技术的尼龙具有更高的强度;
Smart Images

Figure BDA0004507400690000083 
Figure BDA0004507400690000091 
Figure BDA0004507400690000101
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of polyamide products, and relates to a polyamide composition and its application in high-strength transparent polyamide monofilaments. Background Technology
[0002] Polyamide is a general term for a type of high molecular weight polymer containing amide bonds (-CO-NH-). Its commercial name is nylon. Nylon 6 (polycaprolactam) and Nylon 66 (polyhexamethylenediamine adipic acid) are the two most widely used polyamides and can be used for injection molding, spinning, film and monofilament applications.
[0003] When polyamide monofilaments are used in deep-sea fishing lines, the diameter of the monofilament is usually required to be above 1.0 mm, and it must also have high tensile strength and high transparency. High strength facilitates the winding and knotting of the fishing line, while high transparency ensures that the fishing line is not visible to fish during fishing.
[0004] When high tensile strength and high transparency are required for monofilaments, copolyamides are preferred as the main component. This involves mixing two or more monomers that can form homopolymers to synthesize polyamides. A typical example is the copolyamide prepared by polymerizing caprolactam, hexamethylenediamine, and adipic acid monomers, often simply called Nylon 6 / 66. Commercially, Nylon 6 / 66 is commonly used as a raw material for industrial monofilaments. Because its molecular chain is more disordered than that of Nylon 6 and Nylon 66, the amide bonds in Nylon 6 / 66 have a lower ability to form hydrogen bonds, resulting in a lower crystallization rate compared to the two homopolymers under the same conditions. Under the same processing conditions, Nylon 6 / 66 exhibits better and higher transparency than Nylon 6 and Nylon 66 homopolymers. Furthermore, due to the lower crystallization rate, a higher draw ratio can be achieved during monofilament preparation compared to Nylon 6, thus resulting in higher tensile strength.
[0005] Polyamide contains a large number of amide groups in its molecular structure and is a highly polar polymer material. It easily absorbs moisture from the environment, which affects its mechanical strength. When polyamide monofilaments are soaked in water (simulating the application environment of fishing line), dry polyamide will absorb water and become wet polyamide. Water molecules are a very effective plasticizer for polyamide, reducing the interaction forces between polymer chains. Therefore, wet polyamide has a higher elongation but a lower tensile breaking strength.
[0006] To address the aforementioned problems, CN115161797A provides an application of polyamide fibers and polyamide compositions in the textile industry. The patent describes polyamide fibers produced by melt spinning a polyamide composition comprising polyamide 66, metal salts, and acid-binding agents. By modifying the polyamide, it achieves better water absorption capacity and a faster water absorption rate, while maintaining good mechanical properties after water absorption. However, the addition of metal salts such as calcium chloride and acid-binding agents such as calcium stearate in this patent results in completely opaque fibers.
[0007] Therefore, it is of great significance to study a polyamide composition and its application in high-strength transparent polyamide monofilaments to solve the above problems. Summary of the Invention
[0008] The purpose of this invention is to solve the above-mentioned problems existing in the prior art and to provide a polyamide composition and its application in high-strength transparent polyamide monofilament.
[0009] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0010] A polyamide composition, by weight, comprises 100 parts nylon resin, 1.5 to 10 parts polyethylene glycol and 1 to 10 parts water; the number average molecular weight of the polyethylene glycol is 200 to 1000.
[0011] Polyamide monofilaments were prepared by spinning a mixture of nylon resin (PA) and polyethylene glycol (PEG). The polyamide monofilaments were then placed in a constant temperature and humidity chamber at 75°C and 95% humidity to absorb moisture, so that the moisture content of the polyamide monofilaments was equal to that of the polyamide composition. The tensile strength of the polyamide monofilaments with a specific moisture content was measured to be 5.6–6.9 cN / dtex.
[0012] As a preferred technical solution:
[0013] In the polyamide composition described above, the nylon resin is nylon 6 resin, nylon 66 resin, or nylon 6 / 66 resin.
[0014] The polyamide composition described above has a nylon 6 / 66 resin with a melting point of 180–215°C and a relative viscosity (RV value) of 2.7–4.5.
[0015] The polyamide composition described above exhibits higher strength compared to prior art nylon at the same moisture content.
[0016] This invention also provides a transparent polyamide composition for use in an aqueous environment, comprising, by weight, 100 parts of copolynylon resin, 1.5-10 parts of polyethylene glycol, and 1.8-30 parts of alcohol-soluble ternary copolyamide; the number average molecular weight of the polyethylene glycol is 200-1000; wherein, when the amount of polyethylene glycol added is <1.5 parts, the effect on improving strength is not significant; when the amount of polyethylene glycol added is too high (>10 parts), the breaking strength of the prepared monofilament decreases; when the amount of alcohol-soluble ternary copolyamide added is >30 parts, the breaking strength of the prepared polyamide monofilament is low; when the Mn of polyethylene glycol is <200, polyethylene glycol is relatively easy to detach when immersed in water; when the Mn of polyethylene glycol is >1000, the compatibility between polyethylene glycol and copolynylon resin is too poor, the transparency of the prepared monofilament decreases, and opaque white spots appear on the surface.
[0017] As a preferred technical solution:
[0018] The transparent polyamide composition for use in an aqueous environment, as described above, uses nylon 6 / 66 resin as the copolymer nylon resin. The melting point of nylon 6 / 66 resin is 180–215°C, and its relative viscosity (RV value) is 2.7–4.5. As indicated in the literature (J.Appl.Pol.Sci.1970,14,2133-2143), the melting point of nylon 6 / 66 resin reflects the density and strength of hydrogen bonds between molecular chains. Because the regularity of the copolyamide molecular chain is weaker than that of the corresponding homopolymer, the melting point of nylon 6 / 66 resin is lower than that of nylon 6 resin within a certain monomer ratio range. When the melting point of nylon 6 / 66 resin is <180°C, the hydrogen bond density between molecular chains is too low, resulting in low breaking strength of the prepared polyamide monofilament. When the melting point of nylon 6 / 66 resin is >215°C, the regularity of the molecular chain is too high, the crystallization rate is too fast, and the transparency of the prepared monofilament decreases.
[0019] The relative viscosity of nylon 6 / 66 resin affects the dry fiber strength of the polyamide composition, and the strength of the polyamide composition will further decrease after moisture absorption. If the RV value is less than 2.7, the polymer molecular chain entanglement is insufficient, and it is easy to break under external force, resulting in a low breaking strength of the prepared monofilament. If the RV value is greater than 4.5, the viscosity is too high, making processing difficult.
[0020] The transparent polyamide composition for use in an aqueous environment as described above has a relative viscosity (RV value) of 2.4 to 4.0 for the alcohol-soluble terpolymer polyamide. The relative viscosity of the alcohol-soluble terpolymer polyamide will affect the dry fiber strength of the composition, and the strength of the composition will further decrease after moisture absorption. If the relative viscosity is too low, the strength will be too low, and if the relative viscosity is too high, the polyamide will be difficult to melt process.
[0021] The transparent polyamide composition for use in an aquatic environment, as described above, has an alcohol-soluble terpolymer polyamide to polyethylene glycol mass ratio greater than 1.2. When the mass ratio of alcohol-soluble terpolymer polyamide to polyethylene glycol is higher than 1.2, more terpolymer polyamide can help provide stable dispersion of polyethylene glycol in the matrix. The fibers made from the polyamide composition can maintain a high level of mechanical strength in long-term immersion in water, which is very beneficial for applications such as fishing lines.
[0022] The transparent polyamide composition for use in an aqueous environment as described above comprises an alcohol-soluble ternary copolymer polyamide consisting of a first amide structural unit, a second amide structural unit, and a third amide structural unit. The first amide structural unit is a PA6 structural unit, the second amide structural unit is a PA66 structural unit, and the third amide structural unit is one of PA610, PA69, PA12, PA612, and PA11 structural units. Alcohol solubility can be obtained by adjusting a certain proportion of PA6 structural units.
[0023] The present invention also provides the use of a transparent polyamide composition for use in an aqueous environment as described in any of the preceding claims, for the preparation of polyamide monofilaments.
[0024] The polyamide monofilaments made from the transparent polyamide composition have the characteristics of high strength, transparency and high wet strength. The polyamide monofilaments can maintain stable mechanical properties under long-term water immersion. The initial wet fiber strength of the polyamide monofilaments is 6.1 to 6.9 cN / dtex. After soaking for one month, the wet strength retention rate is not less than 71% compared with the initial wet fiber strength, and the strength retention rate is not less than 61% compared with the dry polyamide monofilament strength.
[0025] Invention principle:
[0026] Research based on existing technologies has revealed that polyethylene glycol (PEG) is used as a plasticizer in dry polyamides in some non-aqueous environments, such as films. Plasticizers effectively reduce the modulus of polyamides, making the products softer and facilitating the winding process. When used as a plasticizer, low molecular weight PEG is often chosen, as lower molecular weight provides better intermolecular lubrication. The inventors unexpectedly discovered that polyethylene glycol dispersed in polyamide compositions can help suppress the decrease in strength after immersion in water to form a wet resin. Analysis revealed that this is because the addition of polyethylene glycol provides more hydrogen to form hydrogen bonds with nylon resin, thus replacing water molecules that would otherwise form hydrogen bonds with nylon resin. When the polyamide composition is in a wet environment, polyethylene glycol reduces the density of water penetrating into the polyamide composition and forming hydrogen bonds. Moreover, polyethylene glycol is an oligomer with a certain molecular weight, and compared to the hydrogen bonds formed between water and nylon resin, it also has increased van der Waals forces due to the entanglement of molecular chains. Therefore, it does not seriously affect the mechanical properties of nylon resin, and enables the polyamide monofilaments prepared from the polyamide composition to have higher breaking strength in a wet state.
[0027] PEG-containing polyamide monofilaments exhibited excellent mechanical strength after short-term immersion in water. However, with further extended immersion time, the mechanical strength of the PEG-containing polyamide monofilaments decreased, which is related to the migration and precipitation of PEG during immersion in water. When an alcohol-soluble ternary copolymer polyamide was further introduced into the composition, it was found that the composition did not show a significant decrease in mechanical properties after prolonged immersion. This is related to the compatibility between the components. Nylon 6 / 66 resin has poor alcohol solubility, while PEG is soluble in water. Therefore, PEG is more compatible with water than with nylon 6 / 66 resin. When an alcohol-soluble ternary copolymer polyamide is introduced, PEG has an affinity for it, and the ternary copolymer polyamide has an affinity for nylon 6 / 66 resin, inhibiting the migration and precipitation of PEG.
[0028] Beneficial effects:
[0029] (1) A polyamide composition of the present invention has higher strength than nylon of the prior art at the same moisture content;
[0030] (2) The present invention provides a transparent polyamide composition for use in an aquatic environment, which can maintain a high level of mechanical strength under long-term immersion in water;
[0031] (3) When the transparent polyamide composition of the present invention is used in an aquatic environment to prepare polyamide monofilament, the resulting polyamide monofilament has the characteristics of high tensile strength and high transparency, and is especially suitable for fishing line applications. Detailed Implementation
[0032] The present invention will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0033] The following are some of the substances used in the embodiments of this invention, with different numbers used to distinguish substances of the same type:
[0034] (1) Nylon 6 / 66: Produced by Jiangsu Huafeng 2440D, melting point 193℃, RV=4.0, denoted as A1;
[0035] (2) Nylon 6 / 66: Produced by Jiangsu Huafeng 2533D, melting point 189℃, RV=3.3, denoted as A2;
[0036] (3) Nylon 6 / 66: Ultramid C40LX produced by BASF, with a melting point of 190℃ and RV=4.0, denoted as A3;
[0037] (4) Triethylene glycol: Sinopharm Reagent, Mn is 150;
[0038] (5) Polyethylene glycol: National Pharmaceutical Reagent;
[0039] (6) PA6 / 66 / 610 terpolymer: DuPont 8061, RV=2.8, melting point=160℃, denoted as B0;
[0040] (7) Alcohol-soluble ternary copolymer polyamide B1: In a 29L high-pressure polymerization reactor, add 5800g of caprolactam, 3013g of hexamethylenediamine, 2883g of adipic acid, 1252g of sebacic acid, and 5000g of deionized water, and purge with nitrogen three times; then gradually raise the temperature to 250℃ inside the reactor and maintain the pressure at 0.3MPa for 3 hours; gradually reduce the pressure to atmospheric pressure, maintain the temperature inside the reactor at 255℃, and polymerize at atmospheric pressure for 2 hours, then reduce the pressure to -0.04MPa. a. The negative pressure time is 20 min; nitrogen gas is introduced to pressurize to 0.1 MPa, and the material is discharged and granulated to obtain slices; the obtained slices are extracted in boiling water at 100℃ for 16 h, and finally dried to obtain alcohol-soluble terpolymer polyamide B1; the relative viscosity of the finally obtained alcohol-soluble terpolymer polyamide B1 is 2.68, and the melting point is 165℃; 10 wt% of the resin is dissolved in methanol at 55℃, and after complete dissolution, it is sealed and placed in an environment at 23℃. After 24 h, the solution is still clear and transparent.
[0041] (8) Alcohol-soluble ternary copolymer polyamide B2: In a 29L high-pressure polymerization reactor, add 6050g of caprolactam, 2000g of hexamethylenediamine, 1379g of adipic acid, 1572g of sebacic acid, and 5000g of deionized water, and purge with nitrogen three times; then gradually raise the temperature to 250℃ inside the reactor and maintain the pressure at 0.3MPa for 3 hours; gradually reduce the pressure to atmospheric pressure while maintaining the temperature inside the reactor at 255℃, and polymerize at atmospheric pressure for 2 hours, then reduce the pressure to -0.04MPa. a. The negative pressure time is 20 min; nitrogen gas is introduced to pressurize to 0.1 MPa, and the material is discharged and granulated to obtain slices; the obtained slices are extracted in boiling water at 100℃ for 16 h, and finally dried to obtain alcohol-soluble terpolymer polyamide B2; the final alcohol-soluble terpolymer polyamide B2 has a relative viscosity of 2.80 and a melting point of 155℃; 10 wt% of the resin is dissolved in methanol at 55℃, and after complete dissolution, it is sealed and placed in an environment at 23℃. After 24 h, the solution is still clear and transparent.
[0042] (9) Alcohol-soluble ternary copolymer polyamide B4: In a 29L high-pressure polymerization reactor, add 5000g of caprolactam, 3091g of hexamethylenediamine, 2088g of adipic acid, 2320g of azelaic acid, and 5000g of deionized water, and purge with nitrogen three times; then gradually raise the temperature to 250℃ inside the reactor, and maintain the pressure at 0.3MPa for 3 hours; gradually reduce the pressure to atmospheric pressure, maintain the temperature inside the reactor at 255℃, and polymerize at atmospheric pressure for 2 hours, then reduce the pressure to -0.04M The negative pressure time was 20 min; nitrogen gas was introduced to pressurize to 0.1 MPa, the material was discharged and granulated to obtain slices, the obtained slices were extracted in boiling water at 100℃ for 16 h, and finally dried to obtain alcohol-soluble ternary copolymer polyamide B4; the relative viscosity of the finally obtained alcohol-soluble ternary copolymer polyamide was 2.72, and the melting point was 131℃; 10 wt% of B4 resin was dissolved in methanol at 55℃, and after complete dissolution, it was sealed and placed in an environment at 23℃. After 24 h, the solution was still clear and transparent.
[0043] (10) Alcohol-soluble ternary copolymer polyamide B6: In a 29L high-pressure polymerization reactor, add 5050g of caprolactam, 2020g of hexamethylenediamine, 1688g of adipic acid, 1341g of lauryl diacid, and 5000g of deionized water, and purge with nitrogen three times; gradually raise the temperature to 250℃ inside the reactor, and maintain the pressure at 0.3MPa for 3 hours; gradually reduce the pressure to atmospheric pressure, maintain the temperature inside the reactor at 255℃, and polymerize at atmospheric pressure for 2 hours, then reduce the pressure to -0.04M The negative pressure time was 20 min; nitrogen gas was introduced to pressurize to 0.1 MPa, and the material was discharged and granulated to obtain slices; the obtained slices were extracted in boiling water at 100℃ for 16 h, and finally dried to obtain alcohol-soluble terpolymer polyamide B6; the relative viscosity of the finally obtained alcohol-soluble terpolymer polyamide B6 was 2.72, and the melting point was 141℃; 10 wt% of the resin was dissolved in methanol at 55℃, and after complete dissolution, it was sealed and placed in an environment at 23℃. After 24 h, the solution was still clear and transparent.
[0044] (11) Alcohol-soluble ternary copolymer polyamide B7: In a 29L high-pressure polymerization reactor, add 5050g of caprolactam, 1630g of hexamethylenediamine, 2050g of adipic acid, 1300g of dodecyl lactam, and 5000g of deionized water, and purge with nitrogen three times; gradually raise the temperature to 250℃ inside the reactor, and hold the pressure at 0.3MPa for 3h; gradually reduce the pressure to atmospheric pressure, keep the temperature inside the reactor at 255℃, polymerize at atmospheric pressure for 2h, and then reduce the pressure to -0.04MPa for 20min. Nitrogen gas was introduced and pressurized to 0.1 MPa, and the material was discharged and granulated to obtain chips. The obtained chips were extracted in boiling water at 100℃ for 16 h and dried to obtain alcohol-soluble terpolymer polyamide B7. The final alcohol-soluble terpolymer polyamide B7 had a relative viscosity of 2.66 and a melting point of 121℃. 10 wt% of the resin was dissolved in methanol at 55℃. After complete dissolution, the solution was sealed and placed in an environment at 23℃. After 24 h, the solution was observed to still be clear and transparent.
[0045] (12) Alcohol-soluble ternary copolymer polyamide B8: In a 29L high-pressure polymerization reactor, add 5050g of caprolactam, 1630g of hexamethylenediamine, 2050g of adipic acid, 1300g of 11-aminoundecanoic acid, and 5000g of deionized water, and purge with nitrogen three times; gradually raise the temperature to 250℃ inside the reactor, and hold the pressure at 0.3MPa for 3h; gradually reduce the pressure to atmospheric pressure, maintain the temperature inside the reactor at 255℃, polymerize at atmospheric pressure for 2h, and then reduce the pressure to -0.04MPa for 20min. Nitrogen gas was introduced and pressurized to 0.1 MPa, and the material was discharged and granulated to obtain chips. The obtained chips were extracted in boiling water at 100℃ for 16 h and dried to obtain alcohol-soluble terpolymer polyamide B8. The final alcohol-soluble terpolymer polyamide B8 had a relative viscosity of 2.72 and a melting point of 126℃. 10 wt% of the resin was dissolved in methanol at 55℃. After complete dissolution, the solution was sealed and placed in an environment at 23℃. After 24 h, the solution was observed to still be clear and transparent.
[0046] (13) Non-alcohol-soluble terpolymer polyamide B3: In a 29L high-pressure polymerization reactor, add 3410g caprolactam, 3140g hexamethylenediamine, 2640g adipic acid, 1810.6g sebacic acid, and 5000g deionized water, and purge with nitrogen three times; then gradually raise the temperature to 250℃ inside the reactor, and maintain the pressure at 0.3MPa for 3 hours; gradually reduce the pressure to atmospheric pressure, maintain the temperature inside the reactor at 255℃, and polymerize at atmospheric pressure for 2 hours, then reduce the pressure to -0.0... The pressure was 4 MPa for 20 min; nitrogen gas was introduced to pressurize the pressure to 0.1 MPa, and the material was discharged and granulated to obtain slices; the obtained slices were extracted in boiling water at 100℃ for 16 h, and dried to obtain alcohol-insoluble terpolymer polyamide B3; the final alcohol-insoluble terpolymer polyamide B3 had a relative viscosity of 2.83 and a melting point of 166℃; 10 wt% of the resin was dissolved in methanol at 55℃, and after complete dissolution, it was sealed and placed in an environment at 23℃. After 24 h, the solution was observed to be a milky white gel.
[0047] (14) Preparation of alcohol-insoluble terpolymer polyamide B5: In a 29L high-pressure polymerization reactor, add 9000g of caprolactam, 927.5g of hexamethylenediamine, 6.67g of adipic acid, 695.7g of azelaic acid, and 5000g of deionized water, and purge with nitrogen three times; then gradually raise the temperature to 250℃ inside the reactor, and maintain the pressure at 0.3MPa for 3 hours; gradually reduce the pressure to atmospheric pressure, maintain the temperature inside the reactor at 255℃, and polymerize at atmospheric pressure for 2 hours, then reduce the pressure to -0. The pressure was 0.04 MPa for 20 min; nitrogen gas was introduced to pressurize to 0.1 MPa, and the material was discharged and granulated to obtain slices; the obtained slices were extracted in boiling water at 100℃ for 16 h, and dried to obtain alcohol-insoluble terpolymer polyamide B5; the final alcohol-insoluble terpolymer polyamide B5 had a relative viscosity of 2.72 and a melting point of 131℃; 10 wt% of the resin was dissolved in methanol at 55℃, and after complete dissolution, it was sealed and placed in an environment at 23℃. After 24 h, the solution was observed to be a milky white gel.
[0048] The testing method involved in this invention is as follows:
[0049] (1) Relative viscosity (RV value): tested in a 96 wt% sulfuric acid aqueous solution, the concentration of polyamide in sulfuric acid is c = 0.01 g / ml, and the test temperature is 25℃;
[0050] (2) Melting point: The melting point was determined by DSC method. The program was as follows: first round: 40~280℃, 10℃ / min, constant temperature for 3min; second round: 280~40℃, 10℃ / min; third round: 40~280℃, 10℃ / min; the peak temperature of the third round was recorded as the melting point.
[0051] (3) Breaking strength and modulus: The breaking strength and modulus of the polyamide composition sample were determined. The breaking strength and modulus of the monofilament were tested according to the method of GB / T14344-2008. The surface water was wiped dry before the strength test in the wet state.
[0052] (4) Transparency characterization: The transparency of the polyamide composition sample was evaluated by visual inspection. ◎ represents complete transparency by visual inspection, ○ represents semi-transparent and hazy by visual inspection, and × represents opaque.
[0053] The term "Nylon 6 / 66" refers to a binary copolyamide synthesized by copolymerization of caprolactam, hexamethylenediamine, and adipic acid monomers; the term "Nylon 6 / 66 / 12" refers to a ternary copolyamide synthesized by copolymerization of caprolactam, hexamethylenediamine, adipic acid, and dodecalactam monomers; the naming of other copolyamides follows the above rules.
[0054] The term "polyethylene glycol" is a general term for ethylene glycol polymers containing α,ω-terminated hydroxyl groups.
[0055] The term "dry strength" refers to the tensile breaking strength measured in a sample when the moisture content in the monofilament is ≤0.2wt%.
[0056] The term "initial wet strength" refers to the tensile breaking strength of a sample after the monofilament has been immersed in deionized water at 23°C for 72 hours following preparation. This condition is commonly used for conditioning polyamide monofilaments.
[0057] The term "wet strength after one month of immersion" refers to the tensile breaking strength of a sample after the monofilament has been immersed in deionized water at 23°C for one month. This condition simulates the effect of long-term use in an aquatic environment on the properties of the composition.
[0058] The term "alcohol solubility" refers to the state in which polyamide, when dissolved in methanol at 10 wt%, remains a clear solution after being left at 23°C for 24 hours, reflecting its solubility in small molecule alcohols.
[0059] The term "strength retention" refers to the percentage ratio of wet strength to dry strength after a month of immersion in polyamides, which typically experience a decrease in strength upon absorbing moisture.
[0060] The preparation process of polyamide monofilaments is a well-known technology, generally including two steps: ① Masterbatch preparation: Alcohol-soluble ternary copolymer polyamide and polyethylene glycol are melt-mixed in a screw extruder or kneader, and then cooled, pelletized, and dried to obtain a masterbatch with a high concentration of polyethylene glycol. ② Spinning: The masterbatch is compounded with nylon 6 / 66 resin in a certain proportion and then melt-spun to produce monofilaments. A typical traditional process usually consists of five steps: extrusion, cooling, first drawing, second drawing, and heat setting. The extrusion temperature is generally between 200 and 280°C. Cooling is generally done with water, and the cooling temperature is generally between 0 and 50°C. The first drawing temperature is generally between 60 and 120°C, and the draw ratio is generally between 2.0 and 5.0. The second drawing temperature is generally between 150 and 280°C, and the draw ratio is generally between 1.0 and 3.0. The heat setting temperature is generally between 150 and 280°C, and the draw ratio is generally between 0.9 and 1.0. This process is well-known in the polyamide monofilament industry. When spinning polyamide monofilaments, spinning aids such as lubricants, antioxidants, and UV stabilizers are usually added. The lubricant is selected from one or more of the following: oleamide, erucamide, stearamide, ethylene bis-stearamide (EBS), oxidized polyethylene wax, zinc stearate, calcium stearate, and magnesium stearate. The antioxidant is selected from hindered phenolic, phosphite, and thioether antioxidants, such as antioxidant 1010, antioxidant 1076, antioxidant 168, antioxidant 626, antioxidant PEPQ, antioxidant 245, antioxidant 1098, antioxidant 9228, as well as phosphate, phosphite, and hypophosphite antioxidants. The light stabilizer is selected from benzophenone, benzotriazole, triazine, hindered amine, and other light stabilizers. The light stabilizer is a commercially available light stabilizer used in plastics, commonly from BASF (Germany). and Commercially available grades, etc. This also includes other spinning auxiliaries, which will not be elaborated upon here. These auxiliaries and their uses are well-known within the polyamide monofilament industry.
[0061] The present invention will now be explained using one of the following methods. This process is used to prepare polyamide monofilaments in the embodiments and comparative examples of the present invention, but only for the purpose of facilitating and simplifying the description of the invention. It is not a requirement to follow this procedure and therefore should not be construed as a limitation of the invention. Specifically, as follows:
[0062] In a 35mm diameter twin-screw extruder at a melt temperature of 200℃, terpolymer with alcohol solubility is used as the carrier resin. Polyethylene glycol is added via a liquid metering pump, and after melting and mixing, the mixture is drawn into strands, granulated, and dried to prepare polyethylene glycol masterbatch. Nylon 6 / 66 resin, polyethylene glycol masterbatch, 0.1wt% lubricant EBS (China National Pharmaceutical Group Co., Ltd.), and 0.1wt% antioxidant 1010 (BASF) are mixed uniformly using a high-speed mixer. After mixing, the mixture is poured into the hopper of a 25mm diameter single-screw extruder. The temperature of the single-screw extruder from the feeding end to the die head is set to 240℃, 255℃, 255℃, and 250℃. It is then cooled with cooling water at a temperature of 15℃. After the first stretching with a draw ratio of 4.2, it is heated with 100℃ steam. After the second stretching with a draw ratio of 1.2, it is heated with 250℃ hot air. Then it is heat-set with 230℃ hot air, with a draw ratio of 0.95. Finally, a polyamide monofilament with a diameter of 2.0mm is obtained.
[0063] Examples 1-5
[0064] A polyamide composition, by weight, comprises 100 parts nylon resin, 1.5 to 10 parts polyethylene glycol with a number average molecular weight of 200 to 1000, and 1 to 10 parts water.
[0065] The nylon resin and polyethylene glycol in the polyamide composition were used to prepare polyamide monofilaments. The polyamide monofilaments were then placed in a constant temperature and humidity chamber at 75°C and 95% humidity for moisture absorption, until the moisture content of the polyamide monofilaments was equal to that of the polyamide composition. The breaking strength of the polyamide monofilaments after moisture content adjustment was measured. Specific data are shown in Table 1.
[0066] Table 1
[0067]
[0068]
[0069] Comparative Example 1
[0070] A polyamide composition, essentially the same as in Example 1, except that it does not contain PEG200.
[0071] Comparative Example 2
[0072] A polyamide composition, essentially the same as in Example 2, except that it does not contain PEG400.
[0073] Comparative Example 3
[0074] A polyamide composition, essentially the same as in Example 5, except that it does not contain PEG1000.
[0075] Comparative Example 4
[0076] A polyamide composition, essentially the same as in Example 5, except that PEG1000 is replaced with an equal mass of PEG1200.
[0077] Comparative Example 5
[0078] A polyamide composition, essentially the same as in Example 5, except that triethylene glycol is used instead of PEG1000 in equal mass.
[0079] Comparative Example 6
[0080] A polyamide composition, essentially the same as in Example 5, except that PEG2000 is used instead of PEG1000 in equal mass. Nylon resins and polyethylene glycol from Comparative Examples 1-6 were used to prepare polyamide monofilaments. The polyamide monofilaments were then placed in a constant temperature and humidity chamber at 75°C and 95% humidity for moisture absorption, until the moisture content of the polyamide monofilaments was equal to that of the polyamide composition. Their tensile strength was measured, and the specific data are shown in Table 2.
[0081] Table 2
[0082]
[0083] Based on data from Comparative Examples 1-6, it was found that adding polyethylene glycol (PEG) of a certain molecular weight to polyamide compositions with a moisture content of 1-10 parts can improve the strength of the polyamide. This is because the PEG dispersed in the polyamide helps to suppress the influence of moisture on the strength of the polyamide. The inventors speculate that the addition of PEG provides more hydrogen to form hydrogen bonds with nylon, thus replacing water molecules that would otherwise form hydrogen bonds with nylon. When the composition is in a wet environment, PEG reduces the density of hydrogen bonds formed by water penetrating into the polyamide monofilament. Furthermore, PEG, being an oligomer with a certain molecular weight, also exhibits increased van der Waals forces due to molecular chain entanglement compared to the hydrogen bonds formed between water and nylon resin. Therefore, it does not severely affect the mechanical properties of the nylon resin, resulting in higher tensile strength of the prepared polyamide monofilament in a wet state.
[0084] Examples 6-26
[0085] A transparent polyamide composition for use in an aqueous environment comprises, by weight, 100 parts of copolynylon resin, 1.5 to 10 parts of polyethylene glycol with a number average molecular weight of 200 to 1000, and 1.8 to 30 parts of an alcohol-soluble terpolymer polyamide.
[0086] A transparent polyamide composition suitable for use in an aqueous environment was used to prepare polyamide monofilaments. The resulting polyamide monofilaments maintained stable mechanical properties under long-term immersion in water. The initial wet fiber strength of the polyamide monofilaments was 6.1–6.9 cN / dtex, and the wet strength after one month of immersion was 4.5–5.8 cN / dtex. Specific data are shown in Table 3.
[0087] Table 3
[0088]
[0089]
[0090]
[0091] Comparative Example 7
[0092] A transparent polyamide composition is basically the same as in Example 6, except that an equal mass of PEG200 to 100 parts of nylon 6 / 66 resin is directly added, that is, the polyamide composition does not contain alcohol-soluble ternary copolyamide B1.
[0093] The transparent polyamide composition was used to prepare polyamide monofilaments. The initial wet fiber strength of the polyamide monofilaments was 6.2 cN / dtex; the wet strength of the polyamide monofilaments after soaking in water for 1 month was 2.7 cN / dtex; the transparency of the sample was ◎.
[0094] Comparative Example 8
[0095] A transparent polyamide composition, essentially the same as in Example 10, except that an equal mass of alcohol-insoluble terpolymer polyamide B3 is used instead of alcohol-soluble terpolymer polyamide B1.
[0096] The transparent polyamide composition was used to prepare polyamide monofilaments. The initial wet fiber strength of the polyamide monofilaments was 6.3 cN / dtex; the wet strength of the polyamide monofilaments after soaking in water for 1 month was 2.7 cN / dtex; the transparency of the sample was ◎.
[0097] Comparative Example 9
[0098] A transparent polyamide composition is basically the same as in Example 15, except that an equal mass of PEG400 to 100 parts of nylon 6 / 66 resin is directly added, i.e., the polyamide composition does not contain alcohol-soluble ternary copolyamide B1.
[0099] The transparent polyamide composition was used to prepare polyamide monofilaments. The initial wet fiber strength of the polyamide monofilaments was 6 cN / dtex; the wet strength of the polyamide monofilaments after soaking in water for 1 month was 2.6 cN / dtex; the transparency of the sample was ◎.
[0100] Comparative Example 10
[0101] A transparent polyamide composition, essentially the same as in Example 15, except that an equal mass of alcohol-insoluble terpolymer polyamide B5 is used instead of alcohol-soluble terpolymer polyamide B4.
[0102] The transparent polyamide composition was used to prepare polyamide monofilaments. The initial wet fiber strength of the polyamide monofilaments was 6.5 cN / dtex; the wet strength of the polyamide monofilaments after soaking in water for 1 month was 2.8 cN / dtex; the transparency of the sample was ◎.
[0103] As shown in Comparative Examples 7-10, the wet strength of polyamide monofilaments composed of compositions without alcohol-soluble terpolymers or with non-alcohol-soluble terpolymers decreased significantly after immersion for one month. This is because the alcohol-soluble terpolymers in the system can help improve the compatibility of PEG in the matrix, inhibit the diffusion of PEG into water, and make PEG stably dispersed in the matrix, thereby enabling the polyamide composition to maintain stable strength after long-term immersion in water.
[0104] Comparative Example 11
[0105] A transparent polyamide composition is basically the same as in Example 6, except that an equal mass of alcohol-soluble ternary copolyamide B1 is directly added to 100 parts of nylon 6 / 66 resin, i.e., the polyamide composition does not contain polyethylene glycol.
[0106] The transparent polyamide composition was used to prepare polyamide monofilaments. The initial wet fiber strength of the polyamide monofilaments was 5.3 cN / dtex; the wet strength of the polyamide monofilaments after soaking in water for 1 month was 2.0 cN / dtex; the transparency of the sample was ◎.
[0107] Comparing Comparative Example 11 and Example 6, it can be found that the wet strength of the polyamide monofilament decreased significantly after soaking in water for 1 month. This is because polyethylene glycol in the system is a key additive that improves the breaking strength of the wet polyamide fiber. In the composition system without polyethylene glycol, the alcohol-soluble terpolymer has no effect on the retention rate of the breaking strength of the polyamide monofilament.
[0108] Comparative Example 12
[0109] A transparent polyamide composition, basically the same as in Example 6, except that the amount of alcohol-soluble terpolymer B1 is 1.5 parts.
[0110] The transparent polyamide composition was used to prepare polyamide monofilaments. The initial wet fiber strength of the polyamide monofilaments was 6.3 cN / dtex; the wet strength of the polyamide monofilaments after soaking in water for 1 month was 3.1 cN / dtex; the transparency of the sample was ◎.
[0111] Comparing Comparative Example 12 and Example 6, it can be found that the wet strength of the polyamide monofilament decreased significantly after soaking in water for 1 month. This is because when the content of alcohol-soluble terpolymer copolyamide in the system is less than 1.8 parts, it has no significant effect on improving the wet strength in a long-term water environment.
[0112] Comparative Example 13
[0113] A transparent polyamide composition, basically the same as in Example 6, except that the amount of alcohol-soluble terpolymer B1 is 35 parts.
[0114] The transparent polyamide composition was used to prepare polyamide monofilaments. The initial wet fiber strength of the polyamide monofilaments was 5.5 cN / dtex; the wet strength of the polyamide monofilaments after soaking in water for 1 month was 3.7 cN / dtex; the transparency of the sample was ◎.
[0115] Comparing Comparative Example 13 and Example 6, it can be found that the wet strength of the polyamide monofilament decreased significantly. This is because the content of alcohol-soluble ternary copolyamide in the system is too high, which leads to a decrease in the breaking strength of the polyamide monofilament.
[0116] Comparative Example 14
[0117] A transparent polyamide composition, basically the same as in Example 6, except that the amount of PEG200 is 1 part.
[0118] The transparent polyamide composition was used to prepare polyamide monofilaments. The initial wet fiber strength of the polyamide monofilaments was 5.6 cN / dtex; the wet strength of the polyamide monofilaments after soaking in water for 1 month was 3.6 cN / dtex; the transparency of the sample was ◎.
[0119] Comparing Comparative Example 14 and Example 6, it can be found that the wet strength of the polyamide monofilament decreased significantly. This is because the content of polyethylene glycol in the system is less than 1.5 parts, which has no significant effect on improving the strength of the polyamide monofilament.
[0120] Comparative Example 15
[0121] A transparent polyamide composition, basically the same as in Example 6, except that the amount of PEG200 is 15 parts.
[0122] The transparent polyamide composition was used to prepare polyamide monofilaments. The initial wet fiber strength of the polyamide monofilaments was 5.1 cN / dtex; the wet strength of the polyamide monofilaments after soaking in water for 1 month was 3.5 cN / dtex; the transparency of the sample was ◎.
[0123] Comparing Comparative Example 15 and Example 6, it can be found that the wet strength of the polyamide monofilament decreased significantly. This is because when the content of polyethylene glycol in the system is too high, it leads to a decrease in the breaking strength of the polyamide monofilament.
[0124] Comparative Example 16
[0125] A transparent polyamide composition, essentially the same as in Example 6, except that triethylene glycol is used instead of PEG200 in equal mass.
[0126] The transparent polyamide composition was used to prepare polyamide monofilaments. The initial wet fiber strength of the polyamide monofilaments was 5.5 cN / dtex; the wet strength of the polyamide monofilaments after soaking in water for 1 month was 2.1 cN / dtex; the transparency of the sample was ◎.
[0127] Comparing Comparative Example 16 and Example 6, it can be found that the wet strength of the polyamide monofilament is significantly reduced. This is because even in the polyamide composition containing alcohol-soluble ternary copolyamide, triethylene glycol is relatively easy to detach when soaked in water, resulting in low initial wet fiber strength and low wet strength of the polyamide monofilament after soaking for 1 month.
[0128] Comparative Example 17
[0129] A polyamide composition, essentially the same as in Example 6, except that PEG1200 is used instead of PEG200.
[0130] When polyamide compositions are used to prepare polyamide monofilaments, the transparency of the sample is ×.
[0131] Comparing Comparative Example 17 and Example 6, it can be found that the transparency of the polyamide monofilament has decreased and there are opaque white spots on its appearance. This is because the compatibility between polyethylene glycol and PA6 / 66 components has become too poor.
Claims
1. A transparent polyamide composition for use in an aqueous environment, characterized in that: By weight, it contains 100 parts of copolynylon resin, 1.5 to 10 parts of polyethylene glycol, and 1.8 to 30 parts of alcohol-soluble terpolymer polyamide; the number average molecular weight of polyethylene glycol is 200 to 1000.
2. The transparent polyamide composition for use in an aqueous environment according to claim 1, characterized in that, The copolymer nylon resin is nylon 6 / 66 resin; the melting point of nylon 6 / 66 resin is 180~215℃, and the relative viscosity is 2.7~4.
5.
3. The transparent polyamide composition for use in an aqueous environment according to claim 2, characterized in that, The relative viscosity of alcohol-soluble terpolymer polyamide is 2.4~4.
0.
4. A transparent polyamide composition for use in an aqueous environment according to claim 2, characterized in that, The mass ratio of alcohol-soluble terpolymer polyamide to polyethylene glycol is greater than 1.
2.
5. A transparent polyamide composition for use in an aqueous environment according to claim 2, characterized in that, The alcohol-soluble ternary copolymer polyamide is composed of a first amide structural unit, a second amide structural unit, and a third amide structural unit. The first amide structural unit is a PA6 structural unit, the second amide structural unit is a PA66 structural unit, and the third amide structural unit is one of PA610, PA69, PA12, PA612, and PA11 structural units.
6. The application of a transparent polyamide composition for use in an aqueous environment as described in any one of claims 1 to 5, characterized in that: Used to prepare polyamide monofilaments.
Citation Information
Patent Citations
Polyamide resin composition, polyamide resin film, and method for manufacturing polyamide resin film
JP2010174158A